Kaji Eksperimental Jumlah Blade Turbin Propeler Terhadap Unjuk Kerja Hybrid Wind Turbine - Franklin Ishak; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Hybrid turbine is a combination of two different types of turbines which are still in one axis. This research used a propeller turbine with a 2 meters diameter of an S833 blade profile and combined with a 0.5 meters diameter of venturi turbine (Energy Ball Wind Turbine) with a total of 5 blades. This venturi turbine is placed in front of the propeller turbine. This research varies the number of propeller turbine blades, that are 3.4 and 5 blades. The first test is data retrieval on propeller turbines, then the retrieval of data is carried out on hybrid turbines and the two tests can be compared to the result of performance. From this research, it can be seen that hybrid turbines with 5 propeller blades produce greater generator power than other variations of 1.16 watts at 5 m/s wind speed. However, the energy wind turbine ball produces the largest average increase in generator power that is 28.55% by using 5 propeller blades. Keywords : Propeller turbine, hybrid turbine, energy ball wind turbine